Factors contributed towards work life balance among employees in people management department human resource division Petronas upstream business / Syed Muhamad Hafiz Syed Munshi Afdzaruddin - Syed Munshi Afdzaruddin, Syed Muhamad Hafiz (2014)
Economy hectic movement nowadays demanded employee to struggle on their life in order to meet their life needs. However, many people seems did not know the hazard caused due to much hours spent in workplace. It can be concluded that weekdays were a day that people tend to give their life only at workplace, as remaining days in a week were a time for them to enjoy their life. No more work life balance for mostly workers now day especially for those who work in big city or to be highlighted, to those who work at the big company. Hours of work, level of workloads demanded them to forget their actual life in weekdays. Due of that, there are much more negative impact rather than positive, too much hours spent at workplace could cause negative affect of their performance, than later on will affect the organization productivity. Different people tend to have different need of what factor they seek in order balancing their work. Thus, it depends to how employer or organization to implement a right policies in order to ensure each of their employee at the very positive condition. As result of that, employee would be in very great condition in order express their daily routine either fulfill family needs, or output demand at work place.